2021
DOI: 10.1111/jocd.14324
|View full text |Cite
|
Sign up to set email alerts
|

Fractional versus full ablative CO2 laser in recipient site of non‐cultured melanocytes and keratinocyte transplantation in treatment of vitiligo

Abstract: Background Melanocyte‐keratinocyte transplant procedure (MKTP) or non‐cultured epidermal cell suspension transplantation is a very popular surgical modality for treating stable vitiligo. The recipient‐site preparation is one potential determinant in the repigmentation outcomes. Aim To assess the efficacy of fractional CO2 (FCO2) laser in recipient‐site preparation before MKTP and comparing it to the frequently used full surface laser ablation. Methods This randomized comparative trial included 19 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In Group B, an area of 157.74 cm2 was operated on, leading to a repigmentation of 78.601 cm2 (48.8%). There was no statistically significant difference in the total repigmentation achieved between the two groups Hyperpigmentation, scarring, and reactivation of the disease Jamal-Edine et al [ 46 ] RCT 19 patients 32.05 12:7 vitiligo Transplantation of autologous epidermal melanocyte/keratinocyte cells Each patient had the treated areas divided into two groups at random. One group had a recipient site treated with FCO 2 laser ablation (fractional group), while the other group had a recipient site treated with full surface CO 2 laser ablation (full ablation group) In the study, using FCO 2 laser resulted in excellent repigmentation in 40% of cases, good repigmentation in 35% of cases, and poor repigmentation in 25% of cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Group B, an area of 157.74 cm2 was operated on, leading to a repigmentation of 78.601 cm2 (48.8%). There was no statistically significant difference in the total repigmentation achieved between the two groups Hyperpigmentation, scarring, and reactivation of the disease Jamal-Edine et al [ 46 ] RCT 19 patients 32.05 12:7 vitiligo Transplantation of autologous epidermal melanocyte/keratinocyte cells Each patient had the treated areas divided into two groups at random. One group had a recipient site treated with FCO 2 laser ablation (fractional group), while the other group had a recipient site treated with full surface CO 2 laser ablation (full ablation group) In the study, using FCO 2 laser resulted in excellent repigmentation in 40% of cases, good repigmentation in 35% of cases, and poor repigmentation in 25% of cases.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in the comparison of the preparation of the receptor site between fractional CO 2 and full surface CO 2 methods, excellent repigmentation was observed in 40% and 35% of patients, respectively. Despite the significant improvement in both groups, no significant difference has been noted between the two groups [ 46 ]. Furthermore, in the comparison of the two methods of dermabrasion and microneedling at the transplant site, both methods have shown effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…There was no risk of damage/scarring to the recipient bed. An added benefit is the creation of a recipient bed of uniform depth and which can also be used for concave surfaces 43 …”
Section: Recipient Site Preparationmentioning
confidence: 99%
“…An added benefit is the creation of a recipient bed of uniform depth and which can also be used for concave surfaces. 43…”
Section: Fractional Co 2 Lasermentioning
confidence: 99%
“…30 Fractional CO2 laser ablation has been found to be effective in recipient-site preparation before melanocytekeratinocyte transplant procedure (MKTP), achieving successful repigmentation outcomes. 31 A randomized controlled trial compared different recipient-site preparations before cell suspension transplantation and found that superficial full surface ablation with a depth of 144 μm using a CO2 laser was an effective method. 32 CO2 fractional laser treatment has been found to have a good curative effect in the treatment of vitiligo, with a high efficiency rate and a significant reduction in Th2 and Th17 cytokine levels.…”
Section: Introductionmentioning
confidence: 99%